2022
DOI: 10.5713/ab.21.0369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yarrowia lipolytica supplementation on growth performance, intestinal health and apparent ileal digestibility of diets fed to nursery pigs

Abstract: Objective: The objective was to evaluate the efficacy of increasing supplementation of Yarrowia lipolytica (YL) up to 3.0% replacing 1.6% poultry fat and 0.9% blood plasma for growth performance, intestinal health and nutrient digestibility of diets fed to nursery pigs.Methods: Twenty-four pigs weaned at 24 d of age (initial body weight at 7.2±0.6 kg) were allotted to three dietary treatments (n = 8) based on the randomized complete block. The diets with supplementation of YL (0.0%, 1.5%, and 3.0%, replacing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…After 38 d of feeding, all the pigs were euthanized to remove the gastrointestinal tract to collect digesta from mid-jejunum (3 m after the pyloric duodenal junction; Cheng et al, 2021 ) to measure viscosity; mucosa from mid-jejunum to characterize microbiota composition, inflammatory, and oxidative stress parameters; mid-jejunal tissues to measure morphology and crypt cell proliferation; and ileal digesta (a portion of 30 cm prior to the ileocecal valve) to measure the AID of nutrients. Digesta from mid-jejunum was collected into falcon tubes (50 mL), placed on ice, and immediately carried to the lab to measure viscosity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 38 d of feeding, all the pigs were euthanized to remove the gastrointestinal tract to collect digesta from mid-jejunum (3 m after the pyloric duodenal junction; Cheng et al, 2021 ) to measure viscosity; mucosa from mid-jejunum to characterize microbiota composition, inflammatory, and oxidative stress parameters; mid-jejunal tissues to measure morphology and crypt cell proliferation; and ileal digesta (a portion of 30 cm prior to the ileocecal valve) to measure the AID of nutrients. Digesta from mid-jejunum was collected into falcon tubes (50 mL), placed on ice, and immediately carried to the lab to measure viscosity.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was collected into 8 sets of 0.5 mL polypropylene tubes and stored at −80 °C for further analysis. The sample preparation procedures for analysis were performed as previously described ( Cheng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of TNF-α was measured using an ELISA kit (PTA00; R&D System, Minneapolis, MN, USA) following the procedures of the manufacturer [ 22 ]. The standard had a working range of 0 to 1500 pg/mL with a detection limit for TNF-α at 5 pg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…However, 6% Yarrowia lipolytica, with its high lipid content, resulted in diarrhea in piglets, as well as a reduction in the growth performance of nursery pigs [ 165 ]. In addition, Cheng et al (2022) [ 213 ] demonstrated that 1.5% Yarrowia lipolytica used as energy feeds, replacing poultry fat, maintained intestinal health and growth performance in nursery pigs, while the thick cell wall may reduce nutrient digestibility when supplementing 3% Yarrowia lipolytica . Hatlen et al (2012) [ 206 ] reported that 10 to 30% Yarrowia lipolytica supplemented in fish diets improved feed efficiency and protein and energy retention; however, protein digestibility and energy digestibility were reduced due to the indigestible yeast cell wall.…”
Section: Single-cell Oil (Sco)mentioning
confidence: 99%